1999
DOI: 10.1523/jneurosci.19-12-05085.1999
|View full text |Cite
|
Sign up to set email alerts
|

Single- and Multi-Whisker Channels in the Ascending Projections from the Principal Trigeminal Nucleus in the Rat

Abstract: This study investigated the relationship between axonal projections and receptive field properties of whisker-sensitive cells in the principal trigeminal sensory nucleus of the rat. The labeling of small groups of trigeminothalamic axons with biotinylated dextran amine disclosed two broad classes of axons; a majority of fibers (68%; n ϭ 107) project to a single barreloid of the ventral posteromedial nucleus, and the remaining group includes axons that innervate both the posterior group of the thalamus and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
150
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(165 citation statements)
references
References 31 publications
13
150
2
Order By: Relevance
“…4 A and C). The pattern of VGluT2 innervation at P14 was comparable with those reported for Pr5 axonal terminals in the VPm of adult rats (35,36). These results suggest that the refinement of vibrissal relay synapses in the VPm is associated with pruning of somatic innervation by Pr5 axons.…”
Section: Resultssupporting
confidence: 81%
“…4 A and C). The pattern of VGluT2 innervation at P14 was comparable with those reported for Pr5 axonal terminals in the VPm of adult rats (35,36). These results suggest that the refinement of vibrissal relay synapses in the VPm is associated with pruning of somatic innervation by Pr5 axons.…”
Section: Resultssupporting
confidence: 81%
“…This conclusion is consistent with our previous single-axon tracing study in which we reported that the dorsal part of the VPM receives input from two types of PrV cells: cells with a mono-whisker receptive field that form small clusters of terminals in a single barreloid and large multiwhisker-responsive cells that innervate Po and the dorsalmost sector of multiple barreloids (Veinante and Deschênes, 1999) A previous study already demonstrated that cells in the tail of the barreloids project to S2 and to the dysgranular zone of S1 (Pierret et al, 2000). If cells in the head and core of the barreloids form separate pathways of vibrissal information, one would expect both populations of neurons to also differ in the way they innervate barrel cortex.…”
Section: Input/output Through the Head Of The Barreloidssupporting
confidence: 93%
“…In addition, several anatomical studies have pointed out to a functional specialization of the dorsalmost part of the barreloids that abuts Po (hereinafter referred to as the head of the barreloids). This region receives input from specific sets of PrV, reticular thalamic, and corticothalamic fibers (Bourassa et al, 1995;Deschênes et al, 1998;Veinante and Deschênes, 1999;Désîlets-Roy et al, 2002), and it was also proposed that cells in the head of the barreloids might receive corticothalamic input from the motor cortex (Deschênes et al, 1998). Yet, no physiological study has reported distinct response properties for cells located in the head of the barreloids.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented in in vivo studies that stimulation of whiskers activates both the lemniscal and paralemniscal pathways resulting in responses throughout S1 in both barrels and septa (1,2,14,15). In the paralemniscal pathway, POm receives ascending sensory input from the subnuclei of the spinal trigeminal complex (27,28). POm receives Class 1A input from layer 5 of S1 (29) and also receives input from layers 5 and 6 of S2 (30).…”
Section: Discussionmentioning
confidence: 99%